Guerilla Marketing Practices of Advertising Agencies: An Analysis on Turkey Case - Dahan, Gresi Sanje; Levi, Eser (Istanbul Univ, 2012)
This study investigates guerrilla marketing, the approach which uses media unpredictably or unpredictable places as media in order to attain consumers' attention. The study defines guerrilla marketing as a marketing communication approach that is financially suitable for every type of company and communicates with the consumer through interactive activities as well as distinctive media usage. As for the implementation of guerrilla marketing, two media planning pattern is considered. First pattern is mini-media planning that includes guerrilla PR, word of mouth, out of home and internet; second pattern is maxi-media planning that covers vehicles of mass media. Since advertising agencies have influence on the promotional activities of the advertisers, the agencies are examined in the research part of the study. The research tries to answer which guerrilla marketing activities are suggested by the agencies and in what frequency. As for the result, it is found out that advertising agencies approach to guerrilla marketing differ depending on the medium and the type of the activity.
Keywords: Guerrilla Marketing; Mini-Media Planning; Maksi-Media Planning